Usefulness of Percutaneously Injected Ethylene-Vinyl Alcohol Copolymer in Conjunction with Standard Endovascular Embolization Techniques for Preoperative Devascularization of Hypervascular Head and Neck Tumors: Technique, Initial Experience, and Correlation with Surgical Observations - Gemmete, J.J.; Chaudhary, N.; Pandey, A.; Gandhi, D.; Sullivan, S.E.; Marentette, L.J.; Chepeha, D.B.; Ansari, S.A. (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: Few reports have described the embolization of head and neck lesions by using direct percutaneous techniques. We report our preliminary experience in the direct percutaneous embolization of hypervascular head and neck tumors by using Onyx in conjunction with standard endovascular embolization techniques. We describe the technical aspects of the procedure and its efficacy in reducing intraoperative blood loss. MATERIALS AND METHODS: We retrospectively studied 14 patients (3 females and 11 males; mean age, 33.4 years; range, 11–56 years) with 15 hypervascular tumors of the head and neck that underwent direct percutaneous embolization with Onyx in conjunction with particulate embolization. Nine paragangliomas and 6 JNAs underwent treatment. Documented blood loss was obtained from operative reports in these 15 patients with surgical resection performed 24–48 hours after the embolization. RESULTS: Intratumoral penetration with progressive blood flow stasis was achieved during each injection. A mean of 3.1 needles (20-gauge, 3.5-inch spinal needle) were placed percutaneously into the lesion (range, 1–6). The mean intraoperative blood loss was 780 mL (range, <50–2200 mL). Near total angiographic devascularization was achieved in 13 of 15 tumors. There were no local complications or neurologic deficits from the percutaneous access or embolization of these hypervascular tumors. CONCLUSIONS: In this study, the use of percutaneous injected Onyx in conjunction with standard endovascular embolization techniques in patients with hypervascular head and neck tumors seemed to enhance the ability to devascularize these tumors before operative removal. %AVMarteriovenous malformationCBTcarotid body tumorCTACT angiographyDMSOdimethyl sulfoxideDPEdirect percutaneous embolizationDSAdigital subtraction angiographyEBLestimated blood lossECAexternal carotid arteryEEGelectroencephalogramEVOHethylene-vinyl alcohol copolymerICAinternal carotid arteryJNAjuvenile angiofibromaJUGjugularLCCAleft common carotid arteryMIPmaximum intensity projectionn-BCAn-butyl cyanoacrylatePARAparagangliomaPVApolyvinyl alcoholRCCAright common carotid arteryVAvertebral arteryVMvascular malformation